Metal speciation of the Paraopeba river after the Brumadinho dam failure - Teramoto, Elias H. [UNESP]; Gemeiner, Hendryk [UNESP]; Zanatta, Melina B. T. [UNESP]; Menegario, Amauri A. [UNESP]; Chang, Hung K. [UNESP] (Elsevier B.V., 2021)
On January 25, 2019, a tailings dam at the Corrego do Feijao iron ore mine (Brumadinho, Minas Gerais, southern Brazil) ruptured and released similar to 12 million m(3) of mine tailings into the Paraopeba River, which is an important source of drinking water to a populous region. While water potability due to a strong increase in turbidity has been well documented, possible effects of metal contamination are yet to be addressed. We investigated the speciation of metals in the river water and desorption of metals from sediments as a means of supporting risk assessment, using the diffusive gradient in thin films (DGT) technique. desorption experiments and chemical speciation calculations. The results of the in-situ DGT monitoring revealed that the labile concentrations of metals were low in relation to the respective total and dissolved concentrations. Chemical speciation calculations showed that the heavy metals were not stable in the Paraopeba River. The desorption experiments suggested that sediments may release a limited amount of As and Cu. but large amounts of Mn into the river water. Higher concentrations of Fe and Mn indicated a possible association with the impact of mine tailings. In general, the total metal concentrations during the rainy season were higher than those during the dry season, whereas the reverse was generally the case for labile forms. This pattern reveals that metal speciation is intrinsically dependent on the seasonal variation of the hydrological conditions. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Metal speciation; DGT; Desorption experiments; Geochemical simulation; Brumadinho dam disaster